2015
DOI: 10.1111/pan.12663
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of air‐Q and Ambu Aura‐i for controlled ventilation in infants: a randomized controlled trial

Abstract: We conclude that air-Q may be considered superior to Ambu Aura-i in infants for controlled ventilation as it provides higher airway sealing pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 13 publications
5
15
0
Order By: Relevance
“…The full texts of 118 articles were examined in detail. We included 65 articles in this network meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The full texts of 118 articles were examined in detail. We included 65 articles in this network meta‐analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The trials had a median (range [IQR]) sample size of 60 (27–240 [53–100]). Sevoflurane was administered for anaesthesia induction in 44 studies . There were eight crossover designed studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ambu Aura‐i resembles the Laryngeal Mask Airway Classic and thus has a smaller mask cuff, compared to other newer SGAs. One study in small children found it had lower airway leak pressures than the air‐Q . Although various mask designs over many decades have attempted to prevent epiglottic downfolding, it continues to be a problem, as we will discuss later.…”
Section: Characteristics Of the Perfect Pediatric Sgamentioning
confidence: 96%